The PD-1/PD-L1 pathway: biological background and clinical relevance of an emerging treatment target in immunotherapy. (February 2015) - Muenst, Simone; Soysal, Savas D; Tzankov, Alexandar; Hoeller, Sylvia
<x xml:space="preserve">Abstract</x> Introduction: The co-inhibitory receptor programmed death 1 (PD-1) and its ligands are key regulators in a wide spectrum of immune responses and play a critical role in autoimmunity and self-tolerance as well as in cancer immunology. Emerging evidence suggests that cancer cells might use the PD-1/PD-ligand (PD-L) pathway to escape anti-tumor immunity. Based on this evidence, early phase human clinical trials targeting the PD-1/PD-L pathway are currently underway for multiple human cancers. Areas covered: The role of the PD-1/PD-L pathway in autoimmune disease, viral infections as well as in malignant neoplasms is discussed and an overview of the existing therapeutics as well as the results of clinical trials targeting this pathway in cancer is given. Expert opinion: The PD-1/PD-L pathway represents an important mechanism of immune evasion for malignant neoplasms. Early clinical trials indicate effectiveness of PD-1/PD-L pathway blockade in several solid cancers. However, greater insight into the exact mechanisms by which tumors are able to evade anti-tumor immunity is needed to increase clinical effectiveness, for example by combination blockade of diverse co-inhibitory receptors.